Expression of the immune checkpoint modulator OX40 indicates poor survival in acute myeloid leukemia - Marconato, Maddalena; Kauer, Joseph; Salih, Helmut R.; Märklin, Melanie; Heitmann, Jonas S. (Scientific reports, 2022)
Despite therapeutic advances, mortality of Acute Myeloid Leukemia (AML) is still high. Currently, the determination of prognosis which guides treatment decisions mainly relies on genetic markers. Besides molecular mechanisms, the ability of malignant cells to evade immune surveillance influences the disease outcome and, among others, the expression of checkpoints modulators contributes to this. In AML, functional expression of the checkpoint molecule OX40 was reported, but the prognostic relevance of OX40 and its ligand OX40L axis has so far not been investigated. Here we described expression and prognostic relevance of the checkpoint modulators OX40 and OX40L, analyzed on primary AML cells obtained from 92 therapy naïve patients. Substantial expression of OX40 and OX40L on AML blasts was detected in 29% and 32% of the investigated subjects, respectively, without correlation between the expression of the receptor and its ligand. Whereas OX40L expression was not associated with different survival, patients with high expression levels of the receptor (OX40high) on AML blasts survived significantly shorter than OX40low patients (p = 0.009, HR 0.46, 95% CI 0.24-0.86), which identifies OX40 as novel prognostic marker and a potential therapeutic target in AML patients.